Archaeological Research on the Shores of Valiūniškės Paleolake (Slabada and Būda Sites, South Lithuania) - Šatavičius, Egidijus; Vasiliauskas, Liudvikas; Baubonis, Zenonas (Archaeologia Lituana, 2025)
The article publishes the material of archaeological research of several Stone Age sites carried out on the shores of Valiūniškės paleolake. The publication discusses the hydrological and morphological features of small water bodies, as well as the natural conditions necessary for the settlement of Stone Age people. The article analyses the geomorphology of this area and its development in the late Ice Age and Holocene, describes in detail the stratigraphy of the studied sites and the various erosive processes that intensively influenced it. Although, during the research, the finds were not found in abundance, but these are objects that existed for a short period of time, characterized by the homogeneity of the complex of finds. Based on the information accumulated during the research and the typological-technological criteria of the flint inventory and the dates of radiocarbon, the settlements date back to the end of the Final Palaeolithic (late Swiderian tradition, 10th millennium BC), the Mesolithic-Neolithic boundary (7–5th millennium BC) and the second half of the Early Neolithic (5th millennium BC).